Benefits of laparoscopic trans‐hiatal approach with Heller–Dor surgery in a case of mid‐esophageal diverticulum. Issue 2 (14th November 2022) - Ueno, Shuhei; Ogawa, Ryo; Saito, Masaki; Ito, Sunao; Hayakawa, Shunsuke; Okubo, Tomotaka; Sagawa, Hiroyuki; Tanaka, Tatsuya; Takahashi, Hiroki; Matsuo, Yoichi; Mitsui, Akira; Kimura, Masahiro; et al.
Abstract: Compared to the more common epiphrenic diverticula, those located at the central section of the esophagus are quite rare. Minimally invasive approaches for mid‐esophageal diverticula have lacked standardization. Certain mid‐esophageal diverticula, like epiphrenic diverticula, have been attributed to esophageal motility disorders. Thus, we believe that surgery for esophageal diverticula requires preoperative evaluation of esophageal function, with additional surgery being performed in case of abnormalities. The laparoscopic trans‐hiatal approach has been a common technique for managing epiphrenic diverticula but can also be used for mid‐esophageal diverticula located far from the esophagogastric junction provided that the port location is carefully considered. Laparoscopic surgery is also preferable given that it is a minimally invasive procedure and allows for diverticulum resection and Heller myotomy and Dor surgery to prevent reflux in the same field of view. Hence, laparoscopic surgery may be a beneficial alternative to the traditional thoracic or thoracoabdominal techniques.